2017
DOI: 10.1007/s11064-017-2177-0
|View full text |Cite
|
Sign up to set email alerts
|

Trachyspermum ammi Seeds Supplementation Helps Reverse Scopolamine, Alprazolam and Electroshock Induced Amnesia

Abstract: The present study was designed to explore the beneficial effects of successive 10 days administration of Trachyspermum ammi seed's powder (TASP) along with diet (at the dose of 0.5%, 1.0% and 2.0% w/w) on learning and memory of mice. A total of 306 mice divided in 51 equal groups were employed in the study. Passive avoidance paradigm (PAP) and Object recognition Task (ORT) were employed as exteroceptive models. The brain acetylcholinesterase activity (AChE), serum cholesterol, brain monoaldehyde (MDA), brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In this study, we showed that scopolamine significantly reduced the spatial working memory of rats measured via the Y‐maze test. This agrees with previous reports that scopolamine induces cognitive deficiencies in animals (Akinyemi et al., ; Kwon et al., ; Soni & Parle, ). The Y‐maze test is an experimental behavioral procedure widely used to assess immediate spatial working memory, which is one of the indices of overall cognitive function (de Bruin et al., ; Hamlin, Windels, Boskovic, Sah, & Coulson, ).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we showed that scopolamine significantly reduced the spatial working memory of rats measured via the Y‐maze test. This agrees with previous reports that scopolamine induces cognitive deficiencies in animals (Akinyemi et al., ; Kwon et al., ; Soni & Parle, ). The Y‐maze test is an experimental behavioral procedure widely used to assess immediate spatial working memory, which is one of the indices of overall cognitive function (de Bruin et al., ; Hamlin, Windels, Boskovic, Sah, & Coulson, ).…”
Section: Discussionsupporting
confidence: 94%
“…Acetylcholine is a one of the main neurotransmitter involved in formation of memory, which is degraded by AChE enzyme (Soni & Parle, 2017 ). Ketamine has already been established to reduce the concentration of acetylcholine in hippocampal region of brain by the blockade of nAChR with increase of AChE activity related to cause cognitive symptoms of psychosis (Chatterjee et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Memory session was performed on next day and the animal was observed for 300 s to evaluate the cognitive function of animals. Animals were not provided shocks during the memory session (Soni and Parle, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…NO content in the whole fly tissue homogenate was estimated using the Greiss reagent spectrophotometric based method [36] with slight modifications. Briefly, the reaction mixture consist of 150 μ L of tissue homogenate, 50 μ L of distilled water, and 600 μ L of Greiss reagent (0.1% N -(1-naphthyl)-ethylenediamine dihydrochloride, 1% sulfanilamide, and 2.5% phosphoric acid).…”
Section: Methodsmentioning
confidence: 99%